Behavioral Inhibition in the Second Year of Life Is Predicted by Prenatal Maternal Anxiety, Overprotective Parenting and Infant Temperament in Early Infancy - Mudra, Susanne; Göbel, Ariane; Möhler, Eva; Stuhrmann, Lydia Yao; Schulte-Markwort, Michael; Arck, Petra; Hecher, Kurt; Diemert, Anke (Frontiers in Psychiatry, 2022)
Background: Behavioral inhibition, characterized by shyness, fear and avoidance of novel stimuli, has been linked with internalizing personality traits in childhood, adolescence and early adulthood, and particularly later social anxiety disorder. Little is known about the relevance of potential prenatal precursors and early predictors for the development of inhibited behavior, such as infant vulnerability and family risk factors like parental anxiety and overprotection. Pregnancy-related anxiety has been associated with both infant temperament and maternal overprotective parenting. Thus, the aim of this study was investigating the predictive relevance of prenatal pregnancy-related anxiety for behavioral inhibition in toddlerhood, by considering the mediating role of maternal overprotection and infant distress to novelty. Materials and Method: As part of a longitudinal pregnancy cohort, behavioral inhibition at 24 months postpartum was assessed in N=170 mother-child pairs. Maternal pregnancy-related anxiety was examined in the third trimester of pregnancy, and maternal overprotection and infant distress to novelty at 12 months postpartum. Results: Mediation analysis with two parallel mediators showed that the significant direct effect of pregnancy-related anxiety on child behavioral inhibition was fully mediated by infant distress to novelty (p<.001) and maternal overprotection (p<.05). The included variables explained 26% of variance in behavioral inhibition. A subsequent explorative mediation analysis with serial mediators further showed a significant positive association between distress to novelty and maternal overprotective parenting (p<.05). Conclusion: Results indicate a predictive relevance of both infant and maternal factors for the development of behavioral inhibition in toddlerhood. Mothers who perceived more pregnancy-related anxiety showed more overprotective parenting and had infants with more distress to novelty. Further, mothers being more overprotective reported their child to be more inhibited in toddlerhood. Our findings also indicate the stability of reported infant distress to novelty as one aspect of later behavioral inhibition. Addressing specific forms of parental anxiety from pregnancy on and in interaction with child-related variables seems to be a promising approach for future studies and clinical interventions.